P4.31 Kissing is associated with the source for meeting casual partners: an implication for gonorrhoea transmission and control in men who have sex with men. (8th July 2017) - Priest, David; Fairley, Christopher K; Walker, Sandra; Cornelisse, Vincent J; Chen, Marcus; Bradshaw, Catriona S; Phillips, Tiffany; Chow, Eric PF
Abstract : Introduction: Kissing has been identified as one of the most common sexual practices among men who have sex with men (MSM), and it has also been identified as one of the risk factors for pharyngeal gonorrhoea. We conducted this study to understand the kissing pattern amongst MSM by different sources for meeting partners. Methods: A cross-sectional questionnaire-based study was conducted amongst MSM attending Melbourne Sexual Health Centre between March and September 2015. Participants were asked about the sources they used to meet their casual sexual partners and about their kissing practices in the previous three months. Multivariate logistic regression analyses were performed to determine whether kissing is associated with the source for meeting partners. Results: A total of 753 men completed the questionnaire with a median age of 29 (IQR 25–36). Our results showed that men who met partners at gay bars were 7.3 (95% CI 2.1–25.0) times more likely to kiss their sexual partners and they were less likely (aOR 0.6; 95% CI 0.4–0.8) to have sex-without-kissing partners after adjusting for age and other sources for meeting partners. Men who met partners via smartphone applications were 7.0 (95% CI 3.0–15.9) times more likely to kiss their partners. Kissing was not associated with men who met partners at sex on premises venues (SOPV) and via friends. In contrast, men who met partners at SOPV were 2.3 (95% CI 1.6–3.3) times more likely to have sex-without-kissing partners. Conclusion: There is considerable difference in kissing practices among men who met partners at different locations. Our data suggest kissing may be a more important contributor to gonorrhoea transmission among men who met partners at gay bars, while penile-anal sex may be the major mode of gonorrhoea transmission among men who met partners at SOPV.